Faunal composition of mangrove ecosystems along the east coast (Zoological Records and Reviews, 2023)
Mangrove forests of the Indian east coast, distributed across the Sundarbans delta, the Mahanadi andBrahmani-Baitarani estuaries, the Godavari-Krishna delta, and the Pichavaram and Muthupet mangroves of Tamil Nadu,constitute among the most ecologically productive and biodiverse coastal ecosystems in South Asia. Their faunalcomposition -- encompassing resident and transient fish, crustaceans, molluscs, waterbirds, reptiles, and mammals --performs critical ecosystem services including nursery habitat provision for commercially important species, coastalstorm protection, and carbon sequestration. Despite their significance, comprehensive multi-taxon faunal inventories ofIndian east coast mangroves are scattered across taxonomically focused studies with limited comparative scope. Thisstudy presents an integrated faunal assessment across 32 mangrove survey sites spanning seven major mangrovesystems of the Indian east coast, using standardised fish trawling, crab and mollusc quadrats, waterbird point counts,and herpetofauna transects during pre- and post-monsoon seasons (2020-2022). A total of 486 faunal species aredocumented across six taxonomic groups. Fish (148 species) and waterbirds contributed the highest species richness.The Sundarbans system supports the highest total faunal diversity (284 species), significantly exceeding other systems.Mangrove canopy cover, tidal amplitude, and estuarine salinity range are the strongest predictors of faunal richness.Twenty-eight species are IUCN Threatened, including the Irrawaddy dolphin, estuarine crocodile, and olive ridley seaturtle. Conservation implications and management recommendations for east coast mangrove systems are discussed.
Keywords: mangrove conservation; coastal biodiversity; estuarine crocodile; waterbirds; crustaceans; fish; Sundarbans; faunal diversity; east coast India; mangroves